PENGGUNAAN BAHASA JERMAN DALAM BIDANG PARIWISATA (DEUTSCH FÜR TOURISMUS) - Surya Masniari Hutagalung (EDU-KATA, 2020)
This article describes the use of German in Tourism. The purpose of this presentation is as a follow up to a small part of the results of the tracer study conducted for the development of the Deutsch für Tourismus course, under the research "Contribution of the Tracer Study to the Development of the Deutsch für Tourismus Learning Device". Based on interviews with several German-speaking tour guides, there are some vocabularies that have never been mentioned in German in the field of tourism. The tour guide borrows words from English. Therefore the mapping of the vocabulary is done and described. This article presents the results of the mapping and description of the vocabulary.